Quality management of timely provision of medical care - Anatoliy M. Babich; Natal’ya B. Moskaleva (Статистика и экономика)
The article examines one of the key factors that affect the quality of medical care – the timeliness of medical care. Actuality and necessity of this research emerged in the lack of attention of health authorities, of the scientific community to study, assess the level of quality of care provided to the category of the population as residents of remote, inaccessible, remote small rural settlements; population working or self-organized resting in remote places; the population which is in the short-organized holiday in difficult and remote locations and others.The object of the research of the article is – timely provision of medical care provided by road transport. The subject of research is – mechanisms of improve of quality management organization of health care to the population. The purpose – to analyze the timeliness of provision of medical care to residents of small, remote rural communities and victims of road traffic accidents and other accidents. Present the main reasons of the shortcomings in providing timely of medical care. In article proposes measures to improve the situation.Methodology and theoretical studies conducted by the author include:• analyzing information and data in scientific papers, materials of congresses, conferences, seminars, and study of laws and regulations;• determination of the impact indicator of timeliness of care provided to the population with the use of motor vehicles to measure the quality of care;• a comprehensive analysis of the key indicators of quality of medical services – timely care;• selection of the most significant indicators index provided by road timeliness of care and study of the conditions and forms of their manifestation, the study of their joint and individual impact on the timeliness of the quality of medical services with the ranking indicator of their impact.Outlined a number of reasons for deficiencies in providing timely medical care investigated categories of the population, the authors propose to ensure constant timeliness of care measures.Thus, in the article the key indicator of quality – timely provision of medical assistance to the population. Identifies and examines soindikatory providing a dominant impact on the timeliness of care. Suggestions for improvement of the quality management this indicator.